Physiological responses of orange trees subject to regulated deficit irrigation and partial root drying - Jamshidi, Sajad; Zand-Parsa, Shahrokh; Niyogi, Dev (Irrigation science, 2021)
Variations in climate, crop, and field conditions have caused different results in applying regulated deficit irrigation (DI) and partial root drying irrigation (PRD) for citrus. In this study field grown, Washington Navel orange trees were exposed to RDI and PRD practices at two reduced irrigation levels: 80% and 50% of full water requirement under a semi-arid climate. Applying DI-80 and PRD-80 resulted in a moderate water stress condition for the experimented trees and saved ~ 15% of the seasonal irrigation without significant yield reduction (~ 3 to 5%). Applying DI-50 and PRD-50 saved up to 40% of the seasonal irrigation, but the trees experienced a severe water stress condition with ~ 28% yield reduction in DI-50 and 19% in PRD-50 trees. The fruit weight was not significantly affected by the irrigation techniques, and the yield reduction in DI treatments was attributed to the fruitlet abscission and the lower number of fruits per tree. A higher leaf water potential, more controlled vegetative growth and greater yield resulted from the trees irrigated at 80% irrigation level. Internal fruit composition was equally enhanced in DI and PRD fruits and was more notable at the 50% irrigation level. A more effective drought management mechanism was found in the PRD-treated trees and was more notable and beneficial in the severe water stress level. In high water stress conditions, the soil water content (SWC) had a more remarkable impact on controlling the stomatal response compared to vapor pressure deficit (VPD), while in low water stress conditions, the effect of VPD was more evident.